Principles Of Appropriateness In The Indonesian Insurance Legal System: Study On Demutualization In The Globalization Flow. - Tuti RASTUTI (Indonesia Strategic Sustainability, 2022)
This study examines the application of the principle of decency in the insurance system. The research is descriptive-analytical, which describes the legal insurance system as an object regarding realizing consumer protection for the welfare of the people. The normative juridical approach using the theory of the welfare state, justice, and development law is used as a reference to examine the legal insurance system. The study results show that the application of the principle of propriety has only reached the level of legal substance, which is still chaos, while the other two elements, namely the legal structure and legal culture, are still far from the nature of the legal objectives. Therefore, the concept of the principle of propriety of Indonesian personality is proposed to actualize the legal values that live in society. Furthermore, insurance activities based on the principles of economic democracy are believed to foster public trust as social capital for the development of the insurance system.